2016
DOI: 10.1155/2016/4382687
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Complementary and Alternative Medicine Supplements of Potential Concern during Breast Cancer Chemotherapy

Abstract: Objective. While many Complementary and Alternative Medicines (CAM) are unlikely to interact negatively with conventional oncology treatment, some ingestible CAM substances have biological activities that may reduce the effectiveness of chemotherapy or radiation. This study surveyed women with breast cancer in order to document the extent to which women with breast cancer use these CAM substances of concern concurrently with conventional treatments. Methods. A total of 398 women completed a survey describing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
0
22
0
2
Order By: Relevance
“…Additional information about study procedures available in prior reports describing the cost and content of NO care provided to the NO cohort and reports of describing at-enrollment characteristics of our cohorts. 3 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional information about study procedures available in prior reports describing the cost and content of NO care provided to the NO cohort and reports of describing at-enrollment characteristics of our cohorts. 3 …”
Section: Methodsmentioning
confidence: 99%
“… 1 Some biologically based supplements should be evaluated in light of possible interactions with conventional treatments. 2 , 3 It is estimated that between 50% and 80% of cancer patients supplement their care with CAM treatments, while only a small percentage use naturopathic oncology (NO) and receive care from naturopathic doctors (NDs) with special training in oncology. While there is scientific evidence for many of the CAM treatments patients use, and NO providers offer their patients, a review of the literature found no studies describing the health and health-related quality of life (HRQOL) effects of NO care as commonly practiced in communities.…”
mentioning
confidence: 99%
“…Use of dietary supplements, especially antioxidants, during chemotherapy and radiotherapy can influence the action of these treatments. Our earlier analysis using the same data set showed that women mostly used green tea (15.7%), melatonin (10.8%), vitamin C (11.4%), and vitamin E (10.6%) during these adjuvant treatments [24]. Forty-four percent of women used one or more dietary supplement potentially contraindicated during chemotherapy and 32% used antioxidants during radiation treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Forty-four percent of women used one or more dietary supplement potentially contraindicated during chemotherapy and 32% used antioxidants during radiation treatment. And only 23.8% of the women who used antioxidants discussed their use with their medical doctors, while 42% discussed it with CAM providers [24]. Considering both Receivers and Refusers were self-prescribing most of these supplements except vitamin D and melatonin, it would be important to find out where women get the information about supplement use during cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Außerdem wurde in der Literatur darüber berichtet, dass insbesondere Chemotherapiepatienten versuchen, mithilfe der integrativen Medizin ihre Nebenwirkungen zu vermindern [21,22]. Wir untersuchten daher die Fragestellung, ob bei unseren Patientinnen eine Besserung von Nebenwirkungen konventioneller Therapien und der selbstberichteten Lebensqualität erreicht werden konnte.…”
Section: Diskussionunclassified